STRATEGI DAKWAH DALAM MENGANTISIPASI PENYALAHGUNAAN NARKOBA BAGI SISWA DI SMP NEGERI 14 MAKASSAR (Jurnal Washiyah: Jurnal Kajian Dakwah dah Komunikasi, 2021)
Drugs are substances derived from plants, both synthetic and semi-synthetic, which can cause a decrease or change in consciousness. The purpose of this study was to determine the da'wah strategy carried out in anticipation of drug abuse as well as supporting and inhibiting factors in the prevention of drug abuse at SMP Negeri 14 Makassar. This research shows that the process of anticipating drug abuse at SMP Negeri 14 Makassar is: 1) Collaborating with authorized parties such as the National Narcotics Agency (BNN), POLRES, 2) Commemorating Islamic holidays (Maulid Nabi Muhammmad saw), and 3) Improve the ability of teachers in the teaching and learning process (PBM). As for the response of students of SMP Negeri 14 Makassar to the material of da'wah, namely reaping positive and negative responses from students. The supporting factors in anticipating drug abuse for students of SMP Negeri 14 Makassar are; 1) Principals, 2) Teachers, and 3) Students. The inhibiting factors are 1) Lack of motivation from parents, 2) Environment where people hang out, 3) Technology is increasingly developing. The implications of this study are: 1) With the existence of a da'wah process in anticipating drug abuse in this thesis, it can be used as a guide for people who want to apply various activities that can prevent student deviation while at school. 2) It is hoped that the parties at SMP Negeri 14 Makassar can concentrate more on anticipating drug abuse among their students. Keywords: Da'wah Strategy, Drugs, Drug Abuse Prevention.